Actual aspects of public health policy formation on the example of Ukraine (Bangladesh Journal of Medical Science, 2020)
Our publication is devoted to the evolution of the public health system, its role in public health promotion and determination of the basic notions. According to the definition of the World Health Organization, public health is a science and practice of the diseases prevention, increase in life expectancy and health promotion with the help of the organized actions of the society. Yet in practice, public health formed under difficult conditions. In the article we consider the following questions: stages of public health system formation in the world and in Ukraine; analysis of public health system formation in Ukraine: institutional frameworks and strategic priorities and basic operational public health functions in Ukraine. We propose suggestions on legal procedures state improvement in public health in Ukraine in the context of European integration.Bangladesh Journal of Medical Science Vol.19(3) 2020 p.358-364